Short- and longevity outcome of cyclosporin rescue therapy in severe ulcerative colitis refractory to intravenous corticosteroid treatment - Bernadett Farkas; Peter Bacsur; Anita Bálint; Emese Ivány; Mariann Rutka; Anna Fábián; Zsófia Bősze; Renáta Bor; Zoltán Szepes; Klaudia Farkas; Tamás Molnár (Therapeutic Advances in Gastroenterology)
Background: Many patients with severe ulcerative colitis (UC) fail to respond to first-line corticosteroids and require second-line rescue therapy with cyclosporin (CsA) to avoid colectomy. Objectives: To assess the short- and long-term effectiveness and safety of CsA therapy. Design: A single-center, retrospective study was conducted, including patients who received IV CsA therapy for severe, steroid-refractory UC. Methods: Data on therapeutic response and adverse events (AEs) were reported. The Kaplan-Meier method was used to estimate colectomy-free survival rates. The incidence of inflammatory bowel disease flare-ups and the use of advanced therapies after CsA discontinuation were also assessed. Regression analyses were performed to identify predictors for therapeutic response, colectomy, and AEs with CsA. Results: A total of 92 UC patients (54.4% male, mean age: 40.0 ± 14.0 years) were included with the median follow-up time of 14 years (IQR: 7–18). Clinical response was achieved in 88.0%, and clinical remission was observed in 23.9% of patients after the median 6-day (IQR: 7–5) IV phase. A total of 40.7% of responders experienced clinical remission, whereas 13.6% had endoscopic remission at the time of CsA withdrawal (median after 5 months of therapy). Patients receiving concomitant immunomodulators were more likely to achieve clinical remission with CsA ( p  = 0.002; OR: 6.4). After CsA discontinuation, 23.5% of patients relapsed within 6 months, while 59.3% of patients were started on biologics. The probability of colectomy-free survival was 74.7%, 62.6%, 57.1%, and 45.6% at 1, 3, 5, and 14 years after CsA initiation. AEs were reported in 53.3% of patients, mainly hyperlipidaemia, hypertension, and infections. Hypoalbuminaemia (<35 g/L) at treatment initiation increased the risk of AEs ( p  = 0.03; OR: 0.4), whereas the occurrence of AEs was not associated with concomitant immunomodulator use ( p  = 0.9). Conclusion: CsA may be a potent therapeutic option to induce remission in steroid-refractory, severely active UC, and its effectiveness may be enhanced by the concomitant use of immunomodulators, without compromising safety.